A 2007-2008 Social Accounting Matrix for Pakistan - Debowicz, Dario; Dorosh, Paul A.; Robinson, Sherman; Haider, Syed Hamza (International Food Policy Research Institute, 2012)
This Social Accounting Matrix (SAM) was built for the year 2007–2008 for Pakistan. The proposed approach to estimating SAMs is motivated by an information theoretic approach to estimation (Judge & Mittelhammer, 2012) that takes a Bayesian perspective on the efficient use of information: “Use all the information you have, but do not assume any information you do not have." The methodology used to develop this SAM ensures that it is perfectly consistent with the National Accounts. The SAM includes 51 sectors of activity, 27 factors of production, and 18 household groups, allowing tracing direct and indirect effects of potential scenarios through production and consumption linkages and capture distributional effects. The use of this SAM is illustrated using a semi input-output multiplier model. Output multipliers in Pakistan, accounting for supply constraints, range between 1.1 and 1.4, and shocks to livestock and industry have the largest spillover effects.